Determination of copper in different ethanolic matrices using a chloropropyl silica gel modified with a nanostructured cubic octa(3-aminopropyl)octasilsesquioxane - Do Carmo, Devaney Ribeiro [UNESP]; De Oliveira Bicalho, Urquisa [UNESP]; Silveira, Tayla Fernanda A. [UNESP]; Dias Filho, Newton Luiz [UNESP]; Lataro Paim, Leonardo [UNESP] (Wiley, 2013)
The chloropropyl silica gel was modified with octa(3-aminopropyl) octasilsesquioxane and characterized by Fourier transform infrared (FTIR) spectroscopy, nuclear magnetic resonance (NMR), spectroscopies, and surface and area porosity. The specific sorption capacity of metallic ions (Cu2+ and Ni2+) increases in the following solvent order: water < ethanol 42% < ethanol < ketone. The high values of the constant (K) in the order of 103 L mol-1 suggested the high adsorbent capacity of the modified silica (SGAPC) for Cu2+ and Ni2+. SGAPC was applied to a separation column and shows recoveries of around 100% of copper in samples of sugar cane spirit, vodka, ginger brandy, and ethanol fuel. © 2013 Devaney Ribeiro Do Carmo et al.